1995
DOI: 10.1016/0550-3213(95)00398-c
|View full text |Cite
|
Sign up to set email alerts
|

Towards a singularity-free inflationary universe?

Abstract: We consider the problem of constructing a non-singular inflationary universe in stringy gravity via branch changing, from a previously superexponentially expanding phase to an FRWlike phase. Our approach is based on the phase space analysis of the dynamics, and we obtain a no-go theorem which rules out the efficient scenario of branch changing catalyzed by dilaton potential and stringy fluid sources. We furthermore consider the effects of stringloop corrections to the gravitational action in the form recently … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
139
1

Year Published

1999
1999
2017
2017

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 141 publications
(146 citation statements)
references
References 41 publications
6
139
1
Order By: Relevance
“…It should be noted that these are the defining properties of the (+) and (-) branches. As pointed out in [26], the identification of the (+) branch with the domain of negative times and the (-) branch with that of positive times is just a coincidence. In general, this identification does not necessarily hold, especially when a dilaton potential is present.…”
Section: (-) Branch (Defined In the Domain T > 0)mentioning
confidence: 75%
See 1 more Smart Citation
“…It should be noted that these are the defining properties of the (+) and (-) branches. As pointed out in [26], the identification of the (+) branch with the domain of negative times and the (-) branch with that of positive times is just a coincidence. In general, this identification does not necessarily hold, especially when a dilaton potential is present.…”
Section: (-) Branch (Defined In the Domain T > 0)mentioning
confidence: 75%
“…This assumes the solution of the graceful exit problem which all the tree-level inflationary solutions have to face. In fact, in [26] it is shown that a smooth transition from the (+) to the (-) branch in the low-energy effective theory (that is, to lowest order in the inverse string tension α ′ ), is not possible.…”
Section: Pre-big-bang Cosmologymentioning
confidence: 99%
“…However, due to rather general no-go theorems [14] a smooth connection of these two branches turned out to be impossible, at least without some kind of higher order corrections. In the case of a perfect barotropic fluid, mutually dual solutions (23)- (25) and (31) with barotropic index Γ (cf [17,18]).…”
Section: Model Buildingmentioning
confidence: 99%
“…We find a quasi-isotropic solution for the field equations in the zero approximation (neglecting all spatial gradients) which include both post-big bang and pre-big bang [9,10,11,12] cosmological models. It has been demonstrated [13,14] that a smooth transition from a pre-big bang branch to a post-big bang branch (the graceful exit problem, see also [15,16,17]) is impossible in this approximation, even if we incorporate some dilaton potential, or cosmological constant. We analyze the nature of discontinuities which are contained in cosmological models based on a quasi-isotropic solution with a barotropic perfect fluid as a matter source (cf [18]).…”
Section: Introductionmentioning
confidence: 99%
“…There have been numerous efforts attempting to explore the effects of string theory in cosmology [2] - [21]. One could characterize the main aims of many of these studies as either an attempt to utilize the additional degrees of freedom in the massless sector to induce inflation [2,3,6,7,8,10,11] or developing arguments on the type of modifications to Einstein gravity which are necessary to avoid a cosmological singularity [9,13,14,16,18,19,20].…”
Section: Introductionmentioning
confidence: 99%